hello

negbinomial(x;k,θ)=k/x*binomial(k;x,θ)

how i can prove it??

Printable View

- April 27th 2010, 03:48 AMabdolahprove an equality
hello

negbinomial(x;k,θ)=k/x*binomial(k;x,θ)

how i can prove it?? - April 28th 2010, 12:00 AMmatheagle
what exactly does negbinomial(x;k,θ) mean?

Is it P(X=k) for a NegBi? - April 28th 2010, 12:48 AMabdolah
negbinomail(x;k,θ)=p(x-1,k-1)*θ^k *(1-θ)^(x-k);so that p(x-1,k-1)=combination of k-1 of x-1

Negative binomial distribution - Wikipedia, the free encyclopedia